2008
DOI: 10.31729/jnma.305
|View full text |Cite
|
Sign up to set email alerts
|

Vesicovaginal Fistula at Tertiary Care Center in Eastern Nepal

Abstract: Vesicovaginal fistula is physically, socially and psychologically devastating to the women who suffer from it. The aim of this study is to create some awareness about VVF, to describe the profile of the patients, etiology, and success rate of surgery in our institute. A retrospective analysis of a total of 23 cases of vesicovaginal fistula admitted to the Department of Gynecology and Obstetrics, BPKIHS over a period of three years were included in the study. The cause of VVF in all was obstructed labor except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Given that untreated obstructed labor affects women in many ways and across multiple organ systems [2], which parameters should define a successful outcome? Finally, some avoid the issue altogether by not specifying criteria for success [9]. For other authors, the most important factor is not the anatomic defect, but rather the physiologic problem of incontinence; these writers [6][7][8] define success as dryness or continence after repair.…”
Section: Defining Successmentioning
confidence: 99%
“…Given that untreated obstructed labor affects women in many ways and across multiple organ systems [2], which parameters should define a successful outcome? Finally, some avoid the issue altogether by not specifying criteria for success [9]. For other authors, the most important factor is not the anatomic defect, but rather the physiologic problem of incontinence; these writers [6][7][8] define success as dryness or continence after repair.…”
Section: Defining Successmentioning
confidence: 99%
“…This study showed the teenage pregnancy was not common in our set up contributing 6% of total study group, which is comparable with the study from eastern Nepal. 7 The highest parity in our study was one. Forty three patients (33.9%) had given birth to only one child at the time of presentation.…”
Section: Discussionmentioning
confidence: 45%
“…In the study done in Eastern Nepal it has been reported that, 95.6% Þ stula was due to obstructed labor and 4.4% of gynecological causes. 7 This may be due to the different study region, as in our series, in Kathmandu Model Hospital, there were more number of posthysterectomy Þ stula patients. The age range of the patients in our study was from 10 to 65 years with a mean age of 31.4 years.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations